Ginkgetin: A natural biflavone with versatile pharmacological activities. (November 2020) - Adnan, Muhammad; Rasul, Azhar; Hussain, Ghulam; Shah, Muhammad Ajmal; Zahoor, Muhammad Kashif; Anwar, Haseeb; Sarfraz, Iqra; Riaz, Ammara; Manzoor, Maleeha; Adem, Şevki; Selamoglu, Zeliha
Abstract: Natural products, being richly endowed with curative powers, have become spotlight for biomedical and pharmaceutical research to develop novel therapeutics during recent years. Ginkgetin (GK), a natural non-toxic biflavone, has been shown to exhibit anti-cancer, anti-inflammatory, anti-microbial, anti-adipogenic, and neuroprotective activities. GK combats cancer progression by arresting cell cycle, inducing apoptosis, stimulating autophagy, and targeting many deregulated signaling pathways such as JAK/STAT and MAPKs. GKhalts inflammation mediators like interleukins, iNOS, COX-2, PGE2, NF-κB, and acts as an inhibitor of PLA2. GK shows strong neuroprotection against oxidative stress-promoted cell death, inhibits cerebral micro-hemorrhage, decreases neurologic deficits, and halts apoptosis of neurons. GK also acts as anti-fungal, anti-viral, anti-bacterial, leishmanicidal and anti-plasmodial agent. GK shows substantial preventive or therapeutic effects in in vivo models of many diseases including atherosclerosis, cancer, neurodegenerative, hepatic, influenza, and inflammatory diseases. Based on various computational, in vitro and in vivo evidences, this article demonstrates the potential of ginkgetin for development of therapeutics against various diseases. Although GK has been systematically studied from pharmacological point of view, a vast field of pharmacokinetics, pre-clinical and clinical studies is still open for the researchers to fully validate its potential for the treatment of various diseases.